RETRACTED: Resveratrol Improves Mitochondrial Biogenesis Function and Activates PGC-1α Pathway in a Preclinical Model of Early Brain Injury Following Subarachnoid Hemorrhage - Zhou, Jian; Yang, Zaijia; Shen, Ruiming; Zhong, Wangwang; Zheng, Huiduan; Chen, Zhenggang; Tang, Jianjian; Zhu, Juan (Frontiers in Molecular Biosciences, 2021)
Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) has been shown to play a pivotal role in regulating mitochondrial biogenesis in diseases. Resveratrol (RSV), a natural polyphenolic reagent, has powerful anti-oxidative properties as well as the ability to scavenge mitochondrial reactive oxygen species (ROS) in a variety of central nervous system diseases. However, the underlying molecular mechanisms of RSV on mitochondrial biogenesis in early brain injury (EBI) following subarachnoid hemorrhage (SAH) remain poorly understood. This study aimed to explore the potential neuroprotective effects of RSV on mitochondrial biogenesis and function by activation of the PGC-1α signaling pathway in the prechiasmatic cistern SAH model. PGC-1α expression and related mitochondrial biogenesis were detected. Amounts of nuclear respiratory factor 1 (NRF1) and mitochondrial transcription factor A (TFAM) were determined to evaluate the extent of mitochondrial biogenesis. Increased PGC-1α and mitochondrial biogenesis after SAH were observed in the temporal cortex. Resveratrol increased the expression of PGC-1α, NRF1, and TFAM, and promoted PGC-1α nuclear translocation. Moreover, RSV could scavenge excess ROS, increase the activity of superoxide dismutase (SOD), enhance the mitochondrial membrane potential and ATP levels, reduce the mitochondrial DNA copy number, and decrease the level of malondialdehyde (MDA). RSV significantly ameliorated the release of apoptosis-related cytokines, including P53, cleaved caspase-3, cytochrome c, and BAX, leading to the amelioration of neuronal apoptosis, brain edema, and neurological impairment at 24 h after SAH. These results indicate that resveratrol promotes mitochondrial biogenesis and function by activation of the PGC-1α signaling pathway in EBI following SAH.